Solar light assisted green synthesis of photoreduced graphene oxide for the high-efficiency adsorption of anionic dyes. Issue 84 (21st November 2017) - Gong, Yani; Qin, Chengbing; He, Wenjun; Qiao, Zhixing; Zhang, Guofeng; Chen, Ruiyun; Gao, Yan; Xiao, Liantuan; Jia, Suotang
Abstract : Graphene oxide (GO) with unique physical and chemical properties, such as high specific surface area, chemical stability and environmental friendliness, has been considered as an excellent adsorbent to remove organic dyes from polluted water. Abstract : Graphene oxide (GO) with unique physical and chemical properties, such as high specific surface area, chemical stability and environmental friendliness, has been considered as an excellent adsorbent to remove organic dyes from polluted water. However, because of the electrostatic repulsion between the GO and anionic dyes, the adsorption capacity for anionic dyes is undesirable. Here photoreduced GO (PRGO) was prepared by solar light irradiation and used to investigate the adsorption capacity for anionic dyes. The obtained GO and PRGO were characterized by UV-visible absorption, Raman spectroscopy, atomic force microscopy (AFM), scanning electron microscopy (SEM), Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). The adsorption kinetics and isotherms were evaluated through adsorption experiments of the anionic orange II (OII) dye adsorbed on GO or PRGO. The results revealed that the adsorption was an exothermic process and followed pseudo-second order kinetics. Four more typical anionic dyes, methyl orange (MO), Ponceau S (PS), Azo Rubine (AR), and Trypan Blue (TB), were also used to compare the adsorption capacities between GO and PRGO. It was demonstrated that the adsorption capacity of anionic dyes was significantly enhanced by PRGO, and the maximum enhancement was up to 8 fold. In conclusion, PRGO reduction by solar light irradiation in a green, convenient and cost effective manner, offers promise for the high-efficiency removal of anionic dyes in water treatment.